1995
DOI: 10.1111/j.1365-2672.1995.tb05033.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethanol and temperature on the cellular fatty acid composition of Zygosaccharomyces bailii spoilage yeasts

Abstract: Changes in the fatty acid profile of Zygosaccharomyces bailii strains, isolated from different sources, after growth at increasing concentrations of ethanol and/or decreasing temperatures were determined. Differences in fatty acid composition between Zygosaccharomyces bailii strains at standard conditions (25°C, 0% initial ethanol) were observed and could be related to ethanol tolerance. Zygosaccharomyces bailii strain isolated from wine showed the highest ethanol tolerance in relation to growth rate. Surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These micro‐organisms are relatively common in winery installations and can produce unpleasant odours which cause deterioration of wine flavour ( Chatonnet et al . 1995 ; Couto and Huis in’t Veld 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These micro‐organisms are relatively common in winery installations and can produce unpleasant odours which cause deterioration of wine flavour ( Chatonnet et al . 1995 ; Couto and Huis in’t Veld 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Also, spoilage wine yeasts such as species of Zygossaccaromyces or Dekkera appeared within the total Saccharomyces species population. These micro-organisms are relatively common in winery installations and can produce unpleasant odours which cause deterioration of wine flavour (Chatonnet et al 1995;Couto and Huis in't Veld 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in ethanol tolerance of free S. cerevisiae cells was previously explained through changes in fa y acid composition in cellular membrane (9,(24)(25)(26)(27)(28). Our preliminary studies showed that the mass fractions of palmitic (C16:0), stearic (C18:0), palmitoleic (C16:1) and Table 2.…”
Section: Eff Ects Of Ethanol Stress On Ethanol Formation By Saccharommentioning
confidence: 63%
“…Beales [20] and Russell et al [21] have reported that the cell membrane of both bacteria and yeasts contain higher proportion of unsaturated fatty acids as the growth temperature decreases. Furthermore, a number of less reported alterations can occur such as, shortening in the mean fatty acid chain length, an increase in the amount of branch fatty acids, and a reduction in the proportion of cyclic fatty acids [20][21][22], all related to fatty acids. The decrease in the carbon chain of membrane acids may result in a slight decrease in the deprotonation constant (pK a ) of the corresponding functional group (carboxyl group) as this is the general trend comparing the pK a values of shortchain aliphatic carboxyl acids, e.g.…”
Section: Resultsmentioning
confidence: 99%